57 Methodology validation of using motion-activated cameras to estimate off-highway vehicle park census data and evaluate rider safety behaviours. (9th June 2015) - Jennissen, Charles; Robinson, Emily; Baranow, Eilis; Greene, Gabe; Denning, Gerene
Abstract : Statement of purpose: Safety behaviours of off-highway vehicle (OHV) park users may be better than those riding elsewhere, and census data is required to determine if differences among OHV parks in injuries can be explained by higher use or if other factors are involved. This study's purpose was to ascertain the photographic capture rate of riders entering OHV parks with motion-activated cameras, and to determine study variable concordance between on-site evaluations and photo appraisement. Methods/approach: Panoramic motion-activated cameras were placed at the entrances of all eight public OHV parks in Iowa. On-site assessment and photo image analysis was performed for demographic, vehicle, and safety behaviour variables, and then compared. Results: On-site data collection was performed for 114 h for 17 cameras during which 493 off-road vehicles entered the OHV parks. A total of 251 vehicles entering the parks were identified on photos for an overall capture rate of 50.9%. For cameras with at least 5 vehicles noted during on-site evaluation, the capture rate ranged from 38–81%. The number of vehicles entering the parks was segmented by 15 min intervals, and there was no significant variance or decrease in photo capture rate until there were more than 15 vehicles entering a park during a quarter hour period. Variable concordance between on-site and photo derived data ranged from 91–100% which included sex of rider, estimated age group of rider, vehicle type, number of wheels, number of vehicle riders, helmet use, and restraint use for side-by-side vehicles. Conclusions: About one-half of riders entering Iowa OHV parks were captured by motion-activated cameras. Concordance of study variables was high between that collected on-site and from photo assessment. Significance and contributions: The study validated the use of photo-derived data to determine OHV park users and safety behaviours. Results will also assist in park census estimation.